Hephaestion on metre - Ophuijsen, J. M. van, 1953- (Mnemosyne, Supplements, 1987)
Hephaestion's Encheiridion is the most influential text in the history of metrical scholarship. It has been superseded for some genres of Greek verse but remains basic to the description of others. Its terminology continues to be applied to most of the verse written in Western literary traditions. The present volume offers a translation of th eelliptic Greek text and of a parallel account of metre included in Aristides Quintilianus On Music , with a commentary, an introduction analyzing the approach of ancient metricians in term of their own practical aims, an index of all significant words in the Greek texts, and an English index. The book is designed to be equally accessible to Greekless students of metre and to Greek scholars. It should enable them to take clear stand with regard to the ancient heritage in this field, and to define more unequivocally than has been possible any terms they choose to retain, thereby contributing towards greater coherence and consistency in discussion of poetic metre.